Sinergi Cermat Program: Realizing CSV (Creating Shared Value) through EPR (Extended Producer Responsibility) Based Innovation: Program Sinergi Cermat: Mewujudkan CSV (Creating Shared Value) melalui Inovasi Berbasis EPR (Extended Producer Responsibility) - Navulani, Niwang Gita (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
Sinergi Cermat Program is a sustainability initiative designed to optimize Extended Producer Responsibility (EPR) through various waste utilization innovations and environmental education programs. The program fosters strategic collaboration between corporations, community groups, and local governments. Key outcomes include the implementation of Oligotrik and Charging Stations that empower the Bang Pilo group, as well as the Batik Javing innovation that transforms plastic waste into eco-paving. Moreover, environmental literacy is strengthened through the development of the "Plastik Baik" Digital Module and the "Kawasan Sehati" application. These initiatives not only create shared value (CSV) but also align with government policies on waste management and renewable energy development, demonstrating real synergy among stakeholders in sustainable development efforts.